2016
DOI: 10.1017/cem.2016.16
|View full text |Cite
|
Sign up to set email alerts
|

CAEP 2015 Academic Symposium: Current State and Recommendations to Achieve Adequate and Sustainable Funding for Emergency Medicine Academic Units

Abstract: Objectives: To describe the current state of academic emergency medicine (EM) funding in Canada and develop recommendations to grow and establish sustainable funding. Methods: A panel of eight leaders from different EM academic units was assembled. Using mixed methods (including a literature review, sharing of professional experiences, a survey of current EM academic heads, and data previously collected from an environmental scan), 10 recommendations were drafted and presented at an academic symposium. Attende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…15,16 We found that PEM has a presence in patient care and teaching at 14 of the 17 Canadian medical schools. While university status varies across the country, sites are involved in teaching: undergraduate clerkship programs (8), RCPSC residency programs for PEM (10), off-service residents (14), fellowships (10), and CPD (7). Education scholarship is becoming established, with some sites providing salary support for this endeavour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 We found that PEM has a presence in patient care and teaching at 14 of the 17 Canadian medical schools. While university status varies across the country, sites are involved in teaching: undergraduate clerkship programs (8), RCPSC residency programs for PEM (10), off-service residents (14), fellowships (10), and CPD (7). Education scholarship is becoming established, with some sites providing salary support for this endeavour.…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 Academic Symposium on leadership provided recommendations for current leaders, regarding leadership strategies, governance, and funding. [12][13][14] Although the need for these recommendations is generally accepted among academics, an environmental scan that characterizes each PEM unit in the areas of leadership, administration, education, research, and funding would clearly articulate to the individual sites their specific strengths to build on and weaknesses to address, when comparing themselves to the national averages. Indeed, an environmental scan of (adult) EM academic units was recently published and identified EM academic units without a university status.…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations on the governance of the academic units of EM aim to support the evolution of academic EM and complement the recommendations provided by the funding and leadership panels. 29,30 The Leadership Working Group of the CAEP Academic Section will be addressing each recommendation and will present an update at its next Academic Leadership Symposium to be held in 2018.…”
Section: Next Stepsmentioning
confidence: 99%
“…The three committees of the CAEP Academic Section take turns leading a symposium on education, 6-8 research, [9][10][11][12] or leadership at the CAEP annual conference to present their latest findings and recommendations. [13][14][15] At CAEP 2016, the area of focus was education scholarship with the theme: "The Pathway to Success." The goal of the 2016 Academic Symposium on Education Scholarship was to provide pragmatic recommendations in three areas: 1) recommended training for those pursuing academic roles in EM education, 2) recommendations on how to make an impact in medical education, and 3) the specifics on how to publish in the area of education scholarship.…”
Section: Introductionmentioning
confidence: 99%